PENSUASANAAN RUANG INTERIOR MUSEUM OF SEXUAL ASSAULT BERDASARKAN GRAFIK EMOSI FILM - Bayu Aji Purnawarman; Titihan Sarihati; Setiamurti Rahardjo (Narada : Jurnal Desain dan Seni, 2021)
The rise of cases of violence and sexual harassment in Indonesia has made Indonesia face a crisis in handling violence and sexual harassment. This is due to the lack of public education in this case and the lack of public empathy for the tragedy experienced by the victim and tend to commit victim blaming to the victim which makes stigma and stereotypes still last in the community. Therefore, it is necessary to design a museum that can educate and foster public sympathy which is then expected to reduce the number of cases of violence and sexual harassment in Indonesia. Regarding this, a narrative approach method is used from several film titles with the theme of sexual violence and harassment as well as psychological games which will later produce emotional graphics that are used as guidelines in designing the interior atmosphere of the showroom of the Museum of Sexual Assault. From the graph of these emotions, a storyline is created that will be applied in organizing the types of exhibition areas at the Museum of Sexual Assault.